Validation and typification of Verbascum hybrids (Scrophulariaceae) published by Svante Murbeck and deposited at the Belgrade University Herbarium (BEOU) - Karel Sutorý (Botanica Serbica, 2022)
New nothospecific names were created for six Verbascum hybrids which were previously described by Murbeck without binomials: Verbascum ×ipecensis (V. baldaccii × V. phlomoides), Verbascum ×krusevacense (V. abietinum × V. phlomoides), Verbascum ×lundense (V. herzogii × V. leucophyllum), Verbascum ×petrovicii (V. heuffelii × V. speciosum), Verbascum ×soskae (V. baldaccii × V. pulverulentum), Verbascum ×soskicii (V. longifolium var. pannosum × V. nicolai)